The COVID-19 epidemic! Effect on the Environment and Economy (International Journal of Food and Nutritional Sciences, 2022)
This study examines the current state of knowledge on coronavirus sickness, policy responses to the disease, and its effect on the Indian population, economy, and environment. People's feelings of anxiety and uncertainty have grown because of the epidemic since many people have lost their jobs and income. In addition, there have been more reports of child abuse and domestic abuse because of the government-imposed statewide lockdown. A huge amount of money is lost as a result of the temporary shutdown of the industrial sectors. Some of the industries that were temporarily closed includes , consumer packaged goods, aviation, agriculture, construction, retail, hospitality industry etc textile, gems and jewellery, , manufacturing, and start-ups.As such, the employment prospects of a substantial workforce was jeopardized. The lockdown has helped the ecology recover despite the economic downturn since it has resulted in less pollution and reduced discharge spilling into the water. The policy makers ought to take this as a wake-up call and strategically connect the environment, economy, and population.